VIOLATION MAXIM OF COOPERATION PRINCIPLE OF COMMENTS IN JOEL OSTEEN’S QUOTE ON FACEBOOK - Simamora, Totaria; Zakrimal, Zakrimal (LPPM Universitas Putera Batam, 2020)
Abstract This research primarily focused on violation maxims of cooperative principle on comment in Joel Osteen’s quote in Facebook by using Grace’s theory. This research applied descriptive qualitative method to examine the utterance of comments in Joel’s quote by using observational method and non-participatory technique and as the way collecting the data. The finding data of the research showed; violation of maxim (for telling the rightness, stating, describing, acknowledgment and giving information), the violation of the maxim quantity (for giving information and acceptance), the violation of the maxim relation (for supporting, conclusion, truth, and the importance) and the violation of maxim manner (for asking opinion, encouragement and appointment). The violation of each maxim occurs for some purposes and reasons based on the context and topic.